A Study on Vocational Education in the Field of Culinary Arts to Improve Entrepreneurship Skills Based on Sustainable Development: A Non-Formal Education Perspective - Siti Lutfiah; Norhidayat Norhidayat; Mustangin Mustangin; Wahdatan Nisa (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to examine the culinary training model implemented at LKP Ghanesa in improving culinary-based entrepreneurial skills by analyzing its implementation stages, learning process, instructor competence, entrepreneurial knowledge, business assistance, and their contribution to learners’ economic independence. Methodology: This study employed a qualitative descriptive method. Data were collected using observation, interviews, and document study. The research instruments included interview guides, observation guides, and document checklists. Data were analyzed using the Miles and Huberman Interactive Model. Data validity was ensured through source triangulation and technique triangulation. No software, survey, or branded research tools were used. Main Findings: The culinary training model at LKP Ghanesa was implemented through six systematic stages: program socialization, learning preparation, material delivery, application of learning principles, instructor competence, and program monitoring. The program improved culinary competencies, entrepreneurial knowledge, business readiness, entrepreneurial attitudes, and learners’ economic independence through practical training and business assistance. Novelty/Originality of this study: The novelty of this study lies in its analysis of culinary vocational education as a non-formal education strategy for developing entrepreneurial skills among learners. This study was conducted in only one non-formal education institution, therefore the findings may not represent all vocational education institutions.